Analysis of Cesarean Section at a Tertiary care centre in Eastern Nepal according to Robson's Ten Group classification System (TGCS): A hospital based cross sectional study. (Birat Journal of Health Sciences, 2020)
Introduction: Cesarean sectionis on the rising trend,so WHO proposes that health care facilities uses the Robson's 10 group classification system to audit their Cesarean section rates. This classification will helpto developstrategies to reduce these rates.Objective: The objective of this study was to classify the women coming for delivery into the 10 Robson’s group,to interpret the 10 group classification and to know the highest rate of cesarean section in the group.Methodology: This was a hospital basedcross sectional study carried out in the Department of Obstetrics and Gynaecology, for a period of 6months. All women undergoing deliverywere recruited for study .Based onthe  patient’s obstetric parameters, women were assigned to one of 10 groups as per Robson’s 10-group classification system.The relative size of each group, the cesarean section rate in each group, and the absolute and relative contributions to the overall cesarean section rate was then reported.Results: During the study period, the overall Cesarean Section rate was 33.40%.Highest contribution was by Robson's Group 2(Nulliparous, single cephalic, ≥ 37 weeks, induced or CS before labor(9.84%) followed by Group 1(Nulliparous, single cephalic, ≥ 37 weeks, in spontaneous labor)(7.73%) and Group 5(Previous CS, single cephalic, ≥ 37 weeks)  (5.75%). Least contribution was by Groups 8(All multiple pregnancies (including previous CS)and 9[All abnormal lies (including previous CS)]0.20% and 0.27% respectively. All women in group 9(all abnormal lies including previous CS)had 100% Cesarean rate.Conclusions: With reductions in the primary cesarean section rates and encouragingpatients forVBACcould reduce the contribution of Robson's groups towards the absolute Cesarean Section rates.